Rethinking cultural learning cosmopolitan perspectives on language education - Römhild, Ricardo; Marxl, Anika; Matz, Frauke 1976-; Siepmann, Philipp 1984- (WVT Wissenschaftlicher Verlag Trier, 2023)
"In the multipolar world of the 21st century, successful communication is key, and language education, with its focus on languages, cultures and texts is uniquely positioned to support learners in becoming active agents of change. For global challenges require globally concerted efforts to face and, ultimately, solve these issues. For various reasons discussed in this edited volume, the dominant frameworks of inter- and transcultural learning in English language education have not succeeded in disrupting the perpetuation of systems of categorisation, stereotypisation, and colonial power hierarchies. Thus, the search for more comprehensive notions of cultural learning continues. It is in this context that this volume seeks to reposition cultural learning by exploring cosmopolitan perspectives on language education from a wide range of angles: The contributions in the first part draw on disciplines as diverse as educational philosophy, citizenship education, international law, and human rights education to provide an in-depth discussion, contextualisation, and orientation of cosmopolitan citizenship approaches to English language education. Based on this theoretical foundation, the second part gives an overview of fundamental concepts, principles, and approaches related to a cosmopolitan orientation of cultural learning in English language education. It encompasses a broad spectrum of subjects relevant to the language classroom, from cultural and literary learning to peace education, to fake news, and language variation to sustainability education. In doing so, it offers suggestions for classroom practices to successfully implement cosmopolitan citizenship-informed language education." (Buchrückseite)
Keywords: Englischunterricht; Interkulturelles Lernen; Interkulturelle Erziehung; Language Education / Fremdsprachenerwerb; Cultural Learning / Kulturelles Lernen; Globalisation / Globalisierung; Citizenship Education; Sustainability Education / Nachhaltigkeitserzeihung; Human Rights / Menschenrechte; Cosmopolitan Perspectives / Kosmopolitische Perspektiven; Fake News; Aufsatzsammlung